Stock option taxation and venture capital activity: A cross-country comparison - Magnus Henrekson; Tino Sanandaji (Research Institute of Industrial Economics (IFN), 2016)
One response to uncertainty and transactions costs in VC-finance is to compensate founders (and other key personnel) with stock options under complex contracts. Entrepreneurs are granted stock options contingent on firm performance, vesting and other criteria. While most countries tax stock options as labor earnings, the United States allow them to be taxed at a low capital gains tax rate. The interaction of favorable tax treatment and inherent advantages has led to near universal use of stock options in American venture capital deals, while this remains less common in Europe. The effective tax treatment of stock options depends on tax practices and is not readily observed using statutory tax rates. We asked the local offices of the tax consultancy firm PwC to calculate the effective tax rate for a standardized entrepreneurial case in 22 countries, finding that countries with favorable tax treatment have more VC activity. One advantage of this tax policy is that it narrowly targets entrepreneurial startups without requiring broad tax cuts.
Keywords: L26; H25; H3; K34; 330; Business taxation; Corporate governance; Entrepreneurship; Innovation; Institutions; Tax policy; Venture capital